ShieldTester: Cell-to-Cell Visibility Test for Surface Occluders - Navazo, I.; Rossignac, J.; Jou, J.; Shariff, R. (Computer graphics forum, 2003)
We present a novel Cell‐To‐Cell Visibility (C2CV) algorithm, which given two polyhedra, AandBand a connectedand oriented manifold triangle mesh, S offers a simple, fast and conservative test for detecting when A and B areoccluded from each other by S. Previously disclosed C2CV algorithms either relied on costly occlusion fusion orwere restricted to convex or “apparently convex” occluders, which makes them inappropriate for scenes wherepotential occluders are arbitrary triangulated surfaces, such as the body of a car or a portion of a terrain. Thesimplicity of our C2CV algorithm, named ShieldTester, stems from a new Occlusion Theorem, introduced herewhich permits to establish occlusion by computing the intersection of S with a single ray from a vertex ofAtoa vertex ofB. ShieldTester may be used to establish that pairs of cells in a subdivision of space are hidden fromeach other by a relatively large surface occluder, so that when the viewer is in one cell, the objects in the othercell need not be displayed. Categories and Subject Descriptors (according to ACM CCS): I.3.3 [Computer Graphics]: Computational Geometryand Object Modeling: Occlussion Culling, Visibility Test, Triangle Meshes